Change in screen time and overuse, and their association with psychological well-being among US-wide school-age children during the COVID-19 pandemic: analysis of the National Survey of Children’s Health (NSCH) years 2018–21 - Helena T. Wu; Jiandong Li; Amy Tsurumi (Child and Adolescent Psychiatry and Mental Health, 2024)
Abstract Background Previous studies on screen use and children’s mental health during the Coronavirus Disease 2019 (COVID-19) pandemic focused only on the timeframe during the pandemic, on children between narrow age ranges, only among a subset of children who have previously reported COVID-related severe family economic hardship or worries, or did not distinguish between instructive versus recreational device usage. Thus, in this study, we analyzed trends, specifically related to recreational screen use, and associations with psychological well-being (PWB) in the years before versus during the COVID-19 pandemic, among a wide range of school-aged children, widely across the nation. Methods Using the National Survey of Children’s Health (NSCH) years 2018–21, we analyzed a large random sample of school-aged children (6–17 years old) across the US (n = 88,823). We developed PWB issue scores (PWBIS) using self-reported measures relevant to this age group, and constructed regression models to assess the magnitude of the contribution of the pandemic on recreational screen use and PWB. Results The prevalence of recreational screen overuse and PWBIS increased significantly during the pandemic, compared to prior years. We also detected a notable effect of the pandemic on increased PWBIS, as well as its interaction term finding that it strengthened the association between screen time and PWBIS (p < 0.01 across all regression models). Conclusions Accordingly, our results demonstrate the importance of the pandemic itself as an independent adverse factor and effect measure modifier for screen overuse and PWB more generally among all school-age children widely across the US. Our study used the most current data available, and future studies to evaluate whether these effects are persistent in the years after the pandemic are important.